Pathological Response and Survival in Triple-Negative Breast Cancer Following Neoadjuvant Carboplatin plus Docetaxel - Sharma, P (2018)
Purpose: Prognostic value of pathologic complete response (pCR) and extent of pathologic response attained with anthracycline-free platinum plus taxane neoadjuvant chemotherapy (NAC) in triple-negative breast cancer (TNBC) is unknown. We report recurrence-free survival (RFS) and overall survival (OS) according to degree of pathologic response in patients treated with carboplatin plus docetaxel NAC. Patients and methods: One-hundred and ninety patients with stage I-III TNBC were treated with neoadjuvant carboplatin (AUC6) plus docetaxel (75 mg/m2) every 21 days × 6 cycles. pCR (no evidence of invasive tumor in breast and axilla) and Residual cancer burden (RCB) were evaluated. Patients were followed for recurrence and survival. Extent of pathologic response was associated with RFS and OS using the Kaplan-Meier method. Results: Median age was 51 years, and 52% were node-positive. pCR and RCB I rates were 55% and 13%, respectively. Five percent of pCR patients, 0% of RCB I patients, and 58% of RCB II/III patients received adjuvant anthracyclines. Three-year RFS and OS were 79% and 87%, respectively. Three-year RFS was 90% in patients with pCR and 66% in those without pCR [HR = 0.30; 95% confidence interval (CI), 0.14-0.62; P = 0.0001]. Three-year OS was 94% in patients with pCR and 79% in those without pCR (HR = 0.25; 95% CI, 0.10-0.63; P = 0.001). Patients with RCB I demonstrated 3-year RFS (93%) and OS (100%) similar to those with pCR. On multivariable analysis, higher tumor stage, node positivity, and RCB II/III were associated with worse RFS. Conclusions: Neoadjuvant carboplatin plus docetaxel yields encouraging efficacy in TNBC. Patients achieving pCR or RCB I with this regimen demonstrate excellent 3-year RFS and OS without adjuvant anthracycline.